Energy harvesting from piezoelectric paint films under biaxial strain. (26th March 2020) - Payo, Ismael; Rodriguez, David; Oliva, Jorge; Valverde, Daniel
Abstract: A piezoelectric paint film is proposed as an energy harvester. We analyze the energy generated by the paint as a function of the biaxial strain of the substrate in which the paint is applied. The theoretical study is verified with experimental tests. The piezoelectric paint is composed of piezoelectric powder (lead zirconate titanate) homogeneously distributed in acrylic polymer as binder. The paint is spread on an aluminum substrate with cross shape to allow us to analyze the harvested energy from vibration tests under biaxial strain. We also demonstrate that the harvested energy is linear with the paint film surface area.